Outcome of Minimally Invasive Percutaneous Plate Osteosynthesis Technique for Management of Extra Articular Distal Tibial Fractures - Rahman Rasool Akhtar, Riaz Ahmed, Aamir Nawaz Khan, Omair Ashraf, Ali Ullah Ghauri, Rahman Rasool Akhtar, Riaz Ahmed, Aamir Nawaz Khan, Omair Ashraf, Ali Ullah Ghauri (Journal of Rawalpindi Medical College, 2021)
Objective: To assess the outcome of the minimally invasive percutaneous plate osteosynthesis (MIPPO) method applied for the management of extra-articular distal tibial fractures. Materials and Methods: This quasi-experimental study was conducted at the Department of Orthopaedic Surgery, Benazir Bhutto Hospital, Rawalpindi, Pakistan. Total 57 patients have included extra-articular type A distal tibial fracture, duration of injury <1 week, and competent neurological and vascular status of the fractured site. All the patients were treated with MIPPO Technique by using the distal tibial medial locking plate and the outcome of all patients was assessed radiologically in terms of union and functionally by using the Ovadia-Beals clinical scoring system. Data were analysed by using SPSS v. 21. Results: As per sample size calculation, 57 patients were included with a mean age of 37.19 ± 9.22 years. There were 45 (78.94%) male patients and 12 (21.05%) female patients. According to AO classification; the most common type was 43A1 with 31 patients (54.38%) whereas 18 (31.57%) were in Type 43A2 and 8 (14.03%) in Type 43A3. In our study, fracture union was achieved in a mean duration of 19.6 ± 3.45 weeks. When the functional outcome was analyzed, 41 (71.92%) patients had excellent outcome, 8 (14.03%) had good results, 5 (8.77%) had fair and 3 (5.26%) had poor outcome based on the subjective result and 44 (77.19%) patients had excellent, 7 (12.28%) had good, 3 (5.26%) had fair and 3 (5.26%) had poor result based on an objective result of Ovadia-Beals clinical scoring system. Conclusion: Thus MIPPO can be highly successful in achieving good to excellent outcomes in the maximum number of patients presented with a distal tibia fracture. So in the future, we can rely on this technique for such types of fractures.